Borohydride Reduction Method for PdIn/C Electrocatalysts Synthesis towards Glycerol Electrooxidation under Alkaline Condition - Nandenha, Júlio; Ramos, Carlos Eduardo Domingues; da Silva, Sirlane G.; de Souza, Rodrigo Fernando Brambilla; Fontes, Eric Hossein; Ottoni, Cristiane Angélica [UNESP]; Neto, Almir Oliveira (Wiley, 2021)
Pd−In/C electrocatalysts were synthesized by the adapted borohydride reduction method in different atomic ratios. Electrocatalysts were evaluated by conventional electrochemical techniques and direct glycerol fuel cells. X-ray diffraction profiles indicated the structure of Pd and In (fcc) phases, as well as the presence of In higher oxidation states. Regarding Transmission electron microscopy, it showed the particle‘s average diameters between 6.1–12.7 nm. All PdIn/C electrocatalysts showed high current values for −0.30 V vs. Ag/AgCl, which the best one was PdIn/C 90 : 10. Higher performance for glycerol oxidation was observed in polarization curves at 90 °C for PdIn/C (30 : 70) composition.
Keywords: Direct alkaline fuel cell; electrooxidation reaction; Glycerol; PdIn/C electrocatalysts; polarization curves